Effectiveness of a pharmacist-led quality improvement program to reduce medication errors during hospital discharge - George D; Supramaniam ND; Abd Hamid SQ; Hassali MA; Lim WY; Hss AS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Patients requiring medications during discharge are at risk of discharge medication errors that potentially cause readmission due to medication-related events. Objective: The objective of this study was to develop interventions to reduce percentage of patients with one or more medication errors during discharge. Methods: A pharmacist-led quality improvement (QI) program over 6 months was conducted in medical wards at a tertiary public hospital. Percentage of patients discharge with one or more medication errors was reviewed in the pre-intervention and four main improvements were developed: increase the ratio of pharmacist to patient, prioritize discharge prescription order within office hours, complete discharge medication reconciliation by ward pharmacist, set up a Centralized Discharge Medication Pre-packing Unit. Percentage of patients with one or more medication errors in both pre- and post-intervention phase were monitored using process control chart. Results: With the implementation of the QI program, the percentage of patients with one or more medication errors during discharge that were corrected by pharmacists significantly increased from 77.6% to 95.9% (p<0.001). Percentage of patients with one or more clinically significant error was similar in both pre and post-QI with an average of 24.8%. Conclusions: Increasing ratio of pharmacist to patient to complete discharge medication reconciliation during discharge significantly recorded a reduction in the percentage of patients with one or more medication errors.